The simulation utilization for the bottleneck identification - Petra Vegnerová (Contemporary Economics, 2009)
Advancing globalization increasingly leads to the creation of delivery systems. Increasing competition forces companies to reduce costs permanently. Both of these trends lead to the need to control material and information flows precisely. The target of this article is to describe and show one of ways of bottleneck determination in the supply system. This study deals with the computer simulation and its utilization for assessment of bottleneck.The foundation of the work is created a model of the supply system, it is used to compare the costs associated with the existence of stocks and stock levels in the individual partner of the system, depending on the location of the bottleneck. This article is published as a part of the research intention MSM 6046137306.
Keywords: 330